Maximizing Rituals of Pilgrimage: A Communicative & Cognitive Analysis: تعظيم شعائر الحج: تحليل معرفي تواصلي (المجلة العربية للعلوم و نشر الأبحاث, 2019)
This research seeks revealing the cognitive, value and behavioral dimensions carried by Muslims towards the feelings of pilgrimage, and to study the reality of maximizing the sacred feelings through employ the approaches of cognitive and communicative analysis in testing the nature of knowledge and attitudes and behaviors of the "pilgrims" that is reflected in the there maximizing towards the pilgrimage represented in the rituals and feelings of Hajj. The researcher has adopted an integrated approach between the methods of extrapolation in Shariaa sciences and the methods of analysis in communication and cognitive studies. The research has divided into four main axes, which began with a methodological introduction that defined the nature of the study and the methodological tools used to accomplish it, followed by a conceptual axis known as the most important terminology and a theoretical axis that presented a survey of the relevant literature and a review of previous studies. The fourth axis discussed the aspects of maximization and its purposes. The fourth axis was an extensive discussion of the manifestations of exaltation and purposes, and one of the most important results of the research is that the pilgrimage is a religious corner and a global Islamic cultural phenomenon that have social and cultural influences on the pilgrims lives, The research was divided into four main axes that started with a methodological introduction, a conceptual axis known as the search terms and a theoretical axis provided a survey of the literature and a review of previous relevant studies. The fourth axis provided an extensive discussion of the aspects of glorification and its purposes. In the life of pilgrims, and the implications for the outside world in political and economic relations between Muslims, and commercial transactions between them and other countries and peoples of the world, the pilgrimage has an economic impact in developing the behavior of pilgrims financial and savings, and ended with research with several recommendations, including: For a call to achieve complementarity between the curricula of social and human sciences and the facts of divine revelation, and to define the most important results of that integration and employ it to enhance the places of pilgrimage in places, times, feelings, and rituals for pilgrims. Employing theories and hypotheses of sciences, such as social psychology, communication, and sociology, to study crowds of pilgrims and analyze their regularity, consistency, and communication.